The Relationship Between Males & females in Iraqi Society from the point of view of educated Women: Anthropology Study in the City of Baghdad - Ressen, Aya (Al-Adab Journal, 2024)
The research dealt with the relationship between males and females and the customs and traditions that caused the decline of the female’s status and created an imbalance between the genders in society, as well as the theories explaining gender. The research consisted of two aspects: the first: the theoretical aspect, which includes the problem, importance, goals, concepts, culture, and its impact on society, women, and social authority. As for the second topic, it consists of the biological, social, psychological, and feminist theories that explain gender. As for the second aspect, which is the methodological and field aspect of the study, which includes the method, tool, and fields of research (spatial, temporal, and human), in addition to the research sample, which was represented by (50) educated females in the study population. (Baghdad City). The other topic represents the results of the study, analysis and interpretation of those results from the field side, in addition to the conclusion.